Assessment of bio-intensive management for fruit fly {Bactrocera cucurbitae(Coq.)} of Muskmelon under field condition - Irfan Khan; Babu Lal Yadav; Tej Pratap Singh; Shaitan Singh Rathore; Roop Singh (Annals of Agricultural Research, 2024)
Considering of muskmelon cultivation importance in Chomu block of Jaipur district, an experiment was conducted during summer season (February- May 2021 and 2022) at Jaisinghpura (Chomu) to evaluate field efficacy of Chlorantraniliprole 18.5 SC+ fruit fly trap. Cumulative pooled data on percent fruit infestation showed low fruit infestation (11.14%) in assessed treatment (T2) as compared to farmer practice (T1-17.75%) and control (26.12%). Similarly, two-year cumulative pooled data on number of infested fruit plants-1 exhibited lowest number of fruit infestation i.e. 0.94 fruit plant-1 in assessed treatment as compared to farmer practice (2.03 fruit plant-1) and control (3.31 fruit plant-1). Fruit yield in assessed treatment was 275 qha-1 in the year 2021 and 285 q ha-1 2022. However, the control yield of fruit was 190 and 205 q ha-1 during year 2021 and 2022, respectively. In farmer practice, fruit yield was 250 qha-1 for year 2021 and 240 q ha-1 for 2022, as compared to assessed technology. Net return of assessed technology for the year 2021 was Rs. 4,92,500 ha-1 and that was Rs.1,97,900 ha-1 more as compared to control (Rs.2,94,600 ha-1), however net return of farmer practice was Rs. 4,34,500. Similarly, for the year 2022 net return was Rs. 5,28,300 ha-1, Rs. 4,19,800 ha-1 and Rs. 3,39,300 ha-1 of assessed technology, farmer practice and control, respectively. During the aforesaid year, net return of assessed technology was Rs. 1,89,000 ha-1 higher to control. Economic performance of assessed technology was superior to farmer practice during both the years.